NATO's durability in a post-Cold War world - Burton, Joe (2018)
Why is it that despite the end of the Cold War and the almost constant controversies surrounding the alliance’s role in the world, the North Atlantic Treaty Organization (NATO) is still a prominent and vital player in international security? Joe Burton provides an in-depth analysis of NATO’s changing role in the post–Cold War era and its ability to survive, adapt, and meet the needs of its members in an increasingly turbulent, globalized security environment. He offers a historically and theoretically informed account of NATO that isolates the core dynamics that have held the alliance together in troubled times. In particular, he examines a series of processes and events—from the 1990 Gulf War to the rise of the Islamic State-that help explain NATO’s continuing relevance